Collateral effect of transnational migration: the transformation of medical habitus - Tonatiuh González-Vázquez; César Infante-Xibille; Laura Villa-Torres; Hortensia Reyes-Morales; Blanca Estela Pelcastre-Villafuerte (Instituto Nacional de Salud Pública, 2020)
Objective. To analyze health practice transformations in health providers in Mexico. Materials and methods. We used qualitative data to explore transnational health practices of men with migration experience to the US, healthcare professionals in Mexico from eight rural communities, and Mexican providers in US. Data used came from a study that explored transnational health practices in the context of migration. Results. Healthcare professionals provided care to migrants through remote consultations or via a family member, and in-person during migrants' visits or by healthcare professionals relocating to migrants' destination communities in the US. The remote consultations mainly caused three changes in the field of medical practice: providing care without a patient review or clinical examination, long-distance prescription of medications, and provision of care mediated by a family member. Conclusions. Changes in their medical practice shifted roles of healthcare professionals and of migrants as patients, transforming the hegemonic biomedical model in Mexico.